PKM ABON KULIT PEPAYA DESA PESANGGRAHAN KEC. JANGKAR KAB. SITUBONDO - Eko Hadi Purwanto (INTEGRITAS : Jurnal Pengabdian, 2017)
Papaya is one of the most favorite fruits of community. In addition to its cheap price and the goods are easily to get, papaya also has a good nutritional content and beneficial for it. Papaya fruit contains lots of vitamin A, C, which is very good forhuman body. In addition,Papayais rich in fiber and is very good for health, it turns out that Papaya’s fruit skin is efficacious. When consuming Papaya fruit, most people peel and remove the skin. But in fact, Papaya skin has many benefits; one of them is for health. Based on this reason the idea to usePapaya skin for meal side dish is come out. Not only creating new creations of food but also we are able to provide income from that creation. The science of entrepreneurshipespecially in food business program made from cleaned Papaya’s then produce to be Papaya’s floss. This programis a community service in applying the entrepreneurship activities. This program is expected to help the community of Situbondo to meet the needs of food or side dishes which is tasty, delicious, and hygienic with no preservatives.